SEROLOGICAL EVIDENCE OF EXPOSURE TO Ehrlichia canis IN CATS - Mariana Campos Fontalvo; Isis Assis Braga; Daniel Moura Aguiar; Mauricio Claudio Horta (Ciência Animal Brasileira, 2016)
The aim of the present study was to estimate the occurrence of Ehrlichia canis in cats from the semiarid region of Northeast of Brazil. Sera of 101 healthy cats were submitted by Indirect Immunofluorescence Assay (IFA), and considered positive when antibody titers ? 40 were obtained. Seroprevalence of 35.6% (36/101) was found, with the following titers: 40 (15 animals); 160 (6); 320 (1); 640 (3), and 2,560 (11). No statistical differences were observed when comparing county of origin, gender, age, breed, and modus vivendi (pet and stray cats), and no ticks were observed in any of the cats. This study revealed exposure to E. canis in cats of the Semiarid Northeast of Brazil. Keywords: Caatinga; ehrlichiosis; feline; hemoparasite; semiarid.